Outward propagation velocity and acceleration characteristics in hydrogen-air deflagration. (16th March 2017) - Katsumi, T.; Aida, T.; Aiba, K.; Kadowaki, S.
Abstract: Propagation characteristics of hydrogen-air deflagration need to be understood for an accurate risk assessment. Especially, flame propagation velocity is one of the most important factors. Propagation velocity of outwardly propagating flame has been estimated from burning velocity of a flat flame considering influence of thermal expansion at a flame front; however, this conventional method is not enough to estimate an actual propagation velocity because flame propagation is accelerated owing to cellular flame front caused by intrinsic instability in hydrogen-air deflagration. Therefore, it is important to understand the dynamic propagation characteristics of hydrogen-air deflagration. We performed explosion tests in a closed chamber which has 300 mm diameter windows and observed flame propagation phenomena by using Schlieren photography. In the explosion experiments, hydrogen-air mixtures were ignited at atmospheric pressure and room temperature and in the range of equivalence ratio from 0.2 to 1.0. Analyzing the obtained Schlieren images, flame radius and flame propagation velocity were measured. As the result, cellular flame fronts formed and flame propagations of hydrogen–air mixture were accelerated at the all equivalence ratios. In the case of equivalent ratio φ = 0.2, a flame floated up and could not propagate downward because the influence of buoyancy exceeded a laminar burning velocity. Based upon these propagation characteristics, a favorable estimation method of flame propagation velocity including influence of flame acceleration was proposed. Moreover, the influence of intrinsic instability on propagation characteristics was elucidated. Highlights: Explosion experiments of hydrogen-air mixtures were performed in a closed chamber. Development of a cellular flame front was observed by Schlieren photography using high speed camera. It was shown that flame propagation velocity increases as flame radius increases. It was found that influence of flame acceleration was stronger at lower equivalence ratio. Favorable model of flame acceleration was proposed based on experimental data.